Soil aeration and redox potential as function of pore connectivity unravelled by X‐ray microtomography imaging. (28th October 2021) - Dorau, Kristof; Uteau, Daniel; Hövels, Maren Pia; Peth, Stephan; Mansfeldt, Tim
Abstract: Platinum (Pt)‐tipped electrodes are frequently employed to measure the soil redox potential ( E H ). Thereby, the timely transition from reducing towards oxidising soil conditions is one of the most important biogeochemical changes that can occur in soil. This condition is mainly linked to the air‐filled pore volume ( ε ) and pore geometries. However, even when the Pt electrodes are located in close vicinity to each other, E H readings behave non‐uniformly, presumably due to the millimetre scaled heterogeneity of pore spaces controlling oxygen (O2 ) availability and transport. In this study, we examined the ε distribution and pore connectivity in the close vicinity of a Pt electrode during an artificial evaporation experiment using an undisturbed soil sample (Ah‐horizon, Calcaric Gleysol). We combined physio‐chemical methods with non‐destructive X‐ray computed microtomography (μCT) and 3D‐image analysis. μCT scans were conducted at three‐time points, that is, reducing conditions with E H  < −100 mV (CT‐1), the transition from reducing towards oxidising conditions with an E H increase > 5 mV h −1 (CT‐2), and oxidising conditions with E H  > 300 mV (CT‐3). We observed that the shift from reducing towards oxidising conditions took place at an air‐filled porosity ( ε CT ) of ~0.03 cm 3  cm −3, which matches very with gravimetrically calculated data obtained by tensiometry of ε ~0.05 cm 3  cm −3 . Besides the relation of E H and ε, image analysis revealed that a connected ε CT ( ε CT_conn ) of ~0.02 cm 3  cm −3 is needed to enable enhanced O2 diffusion from the soil surface towards the Pt surface and facilitate a straightforward E H response. We conclude that ε CT_conn is a critical parameter to assess aeration processes in temporarily water‐saturated soils to characterise a switch in redox conditions. Highlights: Usually, soil redox dynamics are related to the air‐filled porosity ( ε CT ) but here its connected portion ( ε CT_conn ) was found more relevant. 3D X‐ray computed microtomography imaging close to a redox electrode enabled us to understand the soil aeration process. Connected ε CT ( ε CT_conn ) of ~0.02 cm 3  cm −3 facilitated oxidising soil conditions. ε CT_conn is a critical parameter to assess the aeration process in temporarily water‐saturated soils.